2022
DOI: 10.1155/2022/7061548
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Malaria in Pregnancy: What Do the Pregnant Women of Nigeria Know and Do about It?

Abstract: Objective. We assessed knowledge, attitude, and practice regarding two malaria prevention measures (long-lasting impregnated mosquito nets, LLINs, and intermittent preventative therapy with sulphadoxine-pyrimethamine (IPTp-SP)) among pregnant women in Nigeria. Methods. Pregnant women selected from among the four communities of Nnewi were interviewed by using a semistructured, interviewer-administered questionnaire on the respondents’ demography, knowledge of the cause, consequences, and malaria prevention meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…However, there was misconception with regard to the vector that transmitted malaria as only 1 to 3rd of the respondents selected mosquitoes as a pathogen vector for malaria. The findings of this study lend credence to those found in earlier research carried out in Nigeria, [23,34,35] Guinea, [28] Tanzania, [29] Ethiopia, [36] and India. [24]…”
Section: Discussionsupporting
confidence: 89%
“…However, there was misconception with regard to the vector that transmitted malaria as only 1 to 3rd of the respondents selected mosquitoes as a pathogen vector for malaria. The findings of this study lend credence to those found in earlier research carried out in Nigeria, [23,34,35] Guinea, [28] Tanzania, [29] Ethiopia, [36] and India. [24]…”
Section: Discussionsupporting
confidence: 89%